1.2e^(-5x) + 2.6 = 3
1.2e^(-5x) = .4
e^(-5x) = .4/(1.2)
e^(-5x) = (1/3)
-5x = ln(1/3)
x = (ln(1/3))/(-5)
x = -(ln(1/3))/(-5)
ANS : (ln(3))/5 or about .21972
2007-01-06 14:17:10
·
answer #1
·
answered by Sherman81 6
·
0⤊
0⤋
Let me see if I can do this...
first subtract 2.6...
1.2e^(-5x)=0.4
then divide 1.2...
e^(-5x)=0.33
then take the natural log of both sides...
ln(e^(-5x))=ln(0.33)
from logrithmic properties, the ln on the left side would cancel out...
-5x=ln(0.33)
divide by -5...
and x=0.2217...
I hope I did that correctly. Check with someone else first.
*haha, I guess someone else got to it before I did.
2007-01-06 14:05:41
·
answer #2
·
answered by mmonkeyccup 2
·
0⤊
0⤋
Move the 2.6 to the other side of the equal sign.
2e^(-5x) = 0.4
Take the natural log of both sides.
ln (2e^(-5x)) = ln 0.4
Simplify the left side.
ln 2 + ln e^(-5x) = ln 0.4
ln e^(-5x) = ln 0.4 - ln 2
The natural log of e^(-5x) is -5x, because ln is log base e.
-5x = ln (0.4 / 2)
-5x = ln (0.2)
x = (1/-5) ln (0.2)
Sorry, I don't have a calculator that can do natural logs with me at the moment.
2007-01-06 14:01:07
·
answer #3
·
answered by Taco girl 2
·
0⤊
0⤋
1.2^5x) = 1.2+2.6=3.8-5x=3 x=8x5=40 1.2^=37 40-37=3
2007-01-06 14:02:46
·
answer #4
·
answered by vanessa 6
·
0⤊
0⤋
1.2e^(-5x)+2.6=3
take ln the both sides.
lne^-6x=ln(0.4)
we know that:
lne^a =a
-6x=-0.91 or x=-0.91/-6
x=0.219922558
2007-01-06 14:13:59
·
answer #5
·
answered by Johnny 2
·
0⤊
0⤋
Solve the (-5x).
2007-01-06 14:01:51
·
answer #6
·
answered by LaLa 4
·
0⤊
0⤋
All the numbers! Just erase them. Just get rid of them. The variables, the decimals, EVERYTHING! They kill my eyes. Die numbers, die!
2007-01-06 13:54:07
·
answer #7
·
answered by Emo 1
·
0⤊
1⤋
maybe it true wat they say "precalculus is hard than calculus" i'm takin calculus honors and i have no idea wat this means lol, maybe because precal breaks everything down step by step
2007-01-06 13:55:28
·
answer #8
·
answered by truemexican 1
·
0⤊
0⤋